Fibrinogen scaffolds with immunomodulatory properties promote in vivo bone regeneration - Daniel Marques Vasconcelos (2016)
The hypothesis behind this work is that fibrinogen (Fg), classically considered a pro-inflammatory protein, can promote bone repair/regeneration. Injury and biomaterial implantation naturally lead to an inflammatory response, which should be under control, but not necessarily minimized. Herein, porous scaffolds entirely constituted of Fg (Fg-3D) were implanted in a femoral rat bone defect and investigated at two important time points, addressing the bone regenerative process and the local and systemic immune responses, both crucial to elucidate the mechanisms of tissue remodelling. Fg-3D led to early infiltration of granulation tissue (6 days post-implantation), followed by bone defect closure, including periosteum repair (8 weeks post-injury). In the acute inflammatory phase (6 days) local gene expression analysis revealed significant increases of pro-inflammatory cytokines IL-6 and IL-8, when compared with non-operated animals. This correlated with modified proportions of systemic immune cell populations, namely increased T cells and decreased B, NK and NIT lymphocytes and myeloid cell, including the Mac 1+ (CD18+/CD11b+) subpopulation. At 8 weeks, Fg-3D led to decreased plasma levels of IL-1 beta and increased TGF-beta 1. Thus, our data supports the hypothesis, establishing a link between bone repair induced by Fg-3D and the immune response. In this sense, Fg-3D scaffolds may be considered immunomodulatory biomaterials.